Internet of Thing Menggunakan Firebase dan Nodemcu untuk Helm Pintar - Prasetyawan, Purwono; Samsugi, Selamet; Prabowo, Rizky (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2021)
The Indonesian government has made laws with the aim of safety in riding, but some people still violate it, especially in wearing standard helmets and riding tired or drowsy. This needs to be campaigned for public awareness. One of the technology trends in the industrial era 4.0 is the Internet of Things (IoT). This article discuss the utilize of IoT innovation to support riders' safety in preventive efforts by designing a smart helmet prototype. This helmet has the intelligence to force the rider to wear the helmet correctly (helmet detection) and alert the rider when drowsiness (drowsiness detection). This study uses an experimental method, applying the Firebase and NodeMCU platforms to present the IoT concept in implementing the smart helmet functionality. The MPU6050 accelerometer is used for drowsiness detection and for helmet detection using a flex sensor with a switch to ensure that the helmet belt is worn properly. The actuator of the helmet detection is a relay (contact to the engine motor), while the drowsiness detection actuator is the buzzer (beep sound). The two smart helmet functionalities run well. The accuracy value for drowsiness detection is 78% and for helmet detection 100%.